Suburban class habitus: applying Pierre Bourdieu's visual sociology to the city. Issue 2 (26th May 2020) - Rajčan, Adam; Burns, Edgar A.
Abstract : Streetscapes of two middle-upper-class suburbs in Melbourne, the State capital city of Victoria, Australia, are photographically compared. Selected pairs of pictures from each streetscape are discussed and contrasted, each pair being considered for how it illustrates one of the five aspects or dimensions in the chosen photographs from the respective suburbs. The near-similarity, yet subtle differences, seen from the street, in the housing and property facades in these suburbs, makes the comparison more difficult, but potentially more useful in terms of Pierre Bourdieu's concept of habitus manifesting not just in people as individuals but in their lived environment. This embodied class imperative is described in interpreting the selected photograph pairs as producing a suburban class habitus in how inhabitants inscribe suburban class distinction into where they live. Using photographs as a methodological tool like Bourdieu means that the point of these visual streetscape representations of each suburb is not summative, deploying the term as a neat or easy label, but aims to be consistent with Bourdieu's approach as a way of investigating the complex socioeconomic and sociocultural mechanisms by which the naturalised class sense is expressed physically in these presentations of self from the street-views they offer.